Overcoming the Underutilisation of Peritoneal Dialysis - Pajek, Jernej (Biomed Res Int, 2015)
Peritoneal dialysis is troubled with declining utilisation as a form of renal replacement therapy in developed countries. We review key aspects of therapy evidenced to have a potential to increase its utilisation. The best evidence to repopulate PD programmes is provided for the positive impact of timely referral and systematic and motivational predialysis education: average odds ratio for instituting peritoneal dialysis versus haemodialysis was 2.6 across several retrospective studies on the impact of predialysis education. Utilisation of PD for unplanned acute dialysis starts facilitated by implantation of peritoneal catheters by interventional nephrologists may diminish the vast predominance of haemodialysis done by central venous catheters for unplanned dialysis start. Assisted peritoneal dialysis can improve accessibility of home based dialysis to elderly, frail, and dependant patients, whose quality of life on replacement therapy may benefit most from dialysis performed at home. Peritoneal dialysis providers should perform close monitoring, preventing measures, and timely prophylactic therapy in patients judged to be prone to EPS development. Each peritoneal dialysis programme should regularly monitor, report, and act on key quality indicators to manifest its ability of constant quality improvement and elevate the confidence of interested patients and financing bodies in the programme.